Polypropylene-polyethylene composition

CN122935573APending Publication Date: 2026-10-16BOREALIS AG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202580021275.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-21
Filing Date
2025-03-19
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,具有易于通过NMR检测的嵌段共聚物特性的塑性体具有相对昂贵的缺点

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to a polypropylene-polyethylene composition having a melt flow rate MFR2 of 1.5 to 50.0 g / 10 min and obtainable by blending a plastic blend (A), a compatibilizer (B) being a C2C4 plastomer, and optionally one or more stabilizers; an article comprising the polypropylene-polyethylene composition; and the use of the compatibilizer (B) in the polypropylene-polyethylene composition for increasing the puncture energy-stiffness (PS) balance of the polypropylene-polyethylene composition to a range of 125% to 500% of the puncture energy-stiffness (PS) balance of the blend (A).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a polypropylene-polyethylene composition having a melt flow rate (MFR2) of 1.5 to 50.0 g / 10 min, and comprising a blended plastic (A), a compatibilizer (B) being a C2C4 plasmon, and optionally one or more stabilizers; articles comprising the polypropylene-polyethylene composition; and the use of said compatibilizer (B) in said polypropylene-polyethylene composition for increasing the puncture energy-stiffness (PS) balance of the polypropylene-polyethylene composition to the puncture energy-stiffness (PS) balance of the blend (A) in the range of 125% to 500%. Background Technology

[0002] In the polyolefins sector, the use of recycled materials from a wide variety of sources is essential. However, all available recycled streams suffer from limited mechanical properties, thus precludeing commercially attractive end uses. Various expensive booster polymers have been proposed for modifying recycled streams, making recycling so uneconomical. For this reason, the market for recycled blends is currently very limited. In blends primarily consisting of polyethylene and polypropylene, higher impact strengths can be achieved relatively easily by adding elastomers acting as compatibilizers, such as conventional ethylene-propylene rubber or EPDM (see Jose et al., J. Polym. Res. 20 (2013) 303). However, this addition limits the stiffness of the resulting composition. Furthermore, many of these elastomers are only available in high molecular weight and / or non-granular forms, the latter requiring specific mixing equipment.

[0003] WO 2015 / 169690 A1 proposes the incorporation of multiphase ethylene-propylene copolymers (HECOs) including ethylene-1-octene copolymers, which are commercially available, particularly from Borealis AG under the trade name Queo®, from DOW Chemical Corp (USA) under the trade name Engage®, or from Exxon Mobil (USA) under the trade name Exact®.

[0004] However, using arbitrary multiphase ethylene-propylene copolymers (HECO) does not yield satisfactory results, particularly in terms of stiffness. It is generally believed that limited stiffness can only be overcome by using plastomers with block copolymer properties (such as Dow Infuse OBC or Intune OBC plastomers provided by Dow Chemical). For example, INTUNE... TMPolypropylene-based OBCs (PP-OBCs) have been designed as compatibilizers rather than elastomers. They contain propylene-rich blocks compatible with polypropylene and ethylene-rich blocks compatible with polyethylene.

[0005] It is easy to understand that block copolymers introduce the option of certain regions with higher stiffness, thereby increasing the overall stiffness. However, plastics with block copolymer properties that are easily detectable by NMR have the disadvantage of being relatively expensive.

[0006] Therefore, there is an urgent need for a good balance between stiffness and good impact in recycled propylene-rich polypropylene-polyethylene blends.

[0007] This invention is based on the surprising discovery that by adding ethylene-1-butene plasmon as a compatibilizer to polypropylene-polyethylene blends, a performance balance with improved stiffness and impact resistance is achieved. Summary of the Invention

[0008] This invention relates to a polypropylene-polyethylene composition comprising:

[0009] a) 75 to 99% by weight, preferably 77 to 98% by weight, more preferably 75 to 95% by weight of a mixed plastic blend (A), wherein the mixed plastic blend (A) comprises:

[0010] A-1) Polypropylene; and

[0011] A-2) Polyethylene,

[0012] The weight ratio of polypropylene to polyethylene is 3:7 to 49:1, preferably 4:6 to 49:1, and more preferably 5:5 to 49:1; and

[0013] b) 1 to 25% by weight, preferably 2 to 23% by weight, more preferably 5 to 20% by weight, of a compatibilizer (B), which is a C2C4 plastic and has the following properties:

[0014] - A melting temperature Tm determined by DSC according to ISO 11357, below 65°C, preferably 25 to 45°C, more preferably 30 to 40°C;

[0015] - A melt flow rate MFR2, measured according to ISO 1133 at a load of 2.16 kg and a temperature of 190 °C, of ​​0.1 to 5.0 g / 10 min, preferably 0.1 to 3.5 g / 10 min, more preferably 0.1 to 2.5 g / 10 min; and

[0016] - 850 to 885 kg / m 3 Preferred weight is 855 to 875 kg / m³.3 More preferably 860 to 870 kg / m 3 The density as determined according to ISO 1183;

[0017] c) 0 to 1.0% by weight of stabilizer or a mixture of stabilizers.

[0018] All quantities are based on the total weight of the polypropylene-polyethylene composition.

[0019] The polypropylene-polyethylene composition has a melt flow rate (MFR2) of 1.5 to 50.0 g / 10 min, preferably 1.7 to 35.0 g / 10 min, and more preferably 2.0 to 25.0 g / 10 min, as determined according to ISO 1133 at a load of 2.16 kg and a temperature of 230 °C.

[0020] Furthermore, the present invention relates to articles comprising polypropylene-polyethylene compositions as described above or below.

[0021] Furthermore, the present invention relates to the use of compatibilizer (B) in polypropylene-polyethylene compositions as described above or below for increasing the puncture energy-stiffness (PS) balance of the polypropylene-polyethylene composition to a range of 125% to 500%, preferably 150% to 300%, of the puncture energy-stiffness (PS) balance of the blend (A).

[0022] The puncture energy-stiffness (PS) balance is the product of the puncture energy measured at 23°C on a 2 mm thick specimen according to ISO 6603-2 and the tensile modulus measured at 23°C according to ISO 527-2.

[0023] definition

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. While any methods and materials similar to or equivalent to those described herein may be used in practice to test the invention, preferred materials and methods are described herein. In describing and claiming protection for this invention, the following terms will be used according to the definitions stated below. Unless otherwise expressly stated, the terms “a”, “an”, etc., are used to mean one or more.

[0025] Blended plastics are defined as polyolefins containing small amounts of compounds not typically present in virgin polypropylene blends (e.g., polystyrene, polyamide, polyester, wood, paper, limonene, aldehydes, ketones, fatty acids, metals, and / or long-term decomposition products of stabilizers). Virgin polypropylene blends are blends derived directly from the production process without any intermediate uses.

[0026] By definition, “mixed plastics” can be equivalent to detectable amounts of polystyrene and / or polyamide-6 and / or limonene and / or fatty acids.

[0027] Blended plastics can thus originate from both post-consumer waste and industrial waste, rather than from the original polymer. Post-consumer waste refers to items that have completed at least their first use cycle (or life cycle), meaning they have been used for their primary purpose. In contrast, industrial waste refers to manufacturing or processing waste that typically does not reach consumers.

[0028] Many different types of polyethylene or polypropylene can be present in “recycled waste.” Specifically, the polypropylene fraction may include: isotactic propylene homopolymers; random copolymers of propylene with ethylene and / or C4-C8 α-olefins; multiphase copolymers comprising propylene homopolymers and / or at least one C2 or C4-C8 α-olefin copolymer; and elastomer fractions comprising copolymers of ethylene with propylene and / or C4-C8 α-olefins, optionally containing a small amount of diene. Examples of components used in the polyethylene fraction are given below.

[0029] As used in this article, “recycled material” refers to material that has been reprocessed from “recycled waste”.

[0030] The term "original" refers to newly produced materials and / or articles that have not yet been recycled before their first use.

[0031] Polymer blends are mixtures of two or more polymer components. Typically, blends are prepared by mixing two or more polymer components. A suitable mixing procedure known in the art is post-polymerization blending. Post-polymerization blending can be a dry blending of polymer components (e.g., polymer powders and / or composite polymer granules) or a melt blending of polymer components by melt mixing.

[0032] The term "polypropylene blend" indicates that the blend primarily comprises polypropylene; however, small amounts of other plastic types are present.

[0033] The term "blended plastic polyethylene blend" indicates that the blend primarily comprises polyethylene; however, small amounts of other plastic types are present.

[0034] Recycled blends, especially post-consumer recycled blends, are almost always mixed plastic blends, reflecting the sorting efficiency in existing recycling methods.

[0035] "Polypropylene-polyethylene composition" refers to a composition containing both polypropylene and polyethylene.

[0036] "Compatibilizers" are substances in polymer chemistry that are added to immiscible polymer blends to improve their stability.

[0037] Polypropylene is a polymer composed of propylene-derived units in an amount of more than 50 mol%.

[0038] Polyethylene is a polymer composed of units derived from ethylene in an amount exceeding 50 mol%.

[0039] The term "C2C4 plastomer" refers to a polymer that combines the properties of an elastomer and a plastic and is composed of structural units derived from monomers derived from ethylene and 1-butene.

[0040] Unless otherwise stated, "%" refers to weight. Detailed Implementation

[0041] This invention relates to a polypropylene-polyethylene composition comprising:

[0042] a) 75 to 99% by weight, preferably 77 to 98% by weight, more preferably 75 to 95% by weight of a mixed plastic blend (A), wherein the mixed plastic blend (A) comprises:

[0043] A-1) Polypropylene; and

[0044] A-2) Polyethylene,

[0045] The weight ratio of polypropylene to polyethylene is 3:7 to 49:1, preferably 4:6 to 49:1, and more preferably 5:5 to 49:1; and

[0046] b) 1 to 25% by weight, preferably 2 to 23% by weight, more preferably 5 to 20% by weight, of a compatibilizer (B), which is a C2C4 plastic and has the following properties:

[0047] - A melting temperature Tm determined by DSC according to ISO 11357, below 65°C, preferably 25 to 45°C, more preferably 30 to 40°C;

[0048] - A melt flow rate MFR2, measured according to ISO 1133 at a load of 2.16 kg and a temperature of 190 °C, of ​​0.1 to 5.0 g / 10 min, preferably 0.1 to 3.5 g / 10 min, more preferably 0.1 to 2.5 g / 10 min; and

[0049] - 850 to 885 kg / m 3 Preferred weight is 855 to 875 kg / m³. 3 More preferably 860 to 870 kg / m 3 The density as determined according to ISO 1183;

[0050] c) 0 to 1.0% by weight of stabilizer or a mixture of stabilizers.

[0051] All quantities are based on the total weight of the polypropylene-polyethylene composition.

[0052] The polypropylene-polyethylene composition has a melt flow rate (MFR2) of 1.5 to 50.0 g / 10 min, preferably 1.7 to 35.0 g / 10 min, and more preferably 2.0 to 25.0 g / 10 min, as determined according to ISO 1133 at a load of 2.16 kg and a temperature of 230 °C.

[0053] Preferably, the total amount of the mixed plastic blend (A), compatibilizer (B), and optional stabilizer or stabilizer mixture accounts for at least 90% by weight of the polypropylene-polyethylene composition, more preferably 100% by weight.

[0054] The polypropylene-polyethylene composition according to the invention has a melt flow rate MFR2 of 1.5 to 50.0 g / 10 min, preferably 1.7 to 35.0 g / 10 min, more preferably 2.0 to 25.0 g / 10 min, as determined according to ISO 1133 at a load of 2.16 kg and a temperature of 230 °C.

[0055] Surprisingly, the polypropylene-polyethylene composition according to the present invention exhibits a good balance of performance in terms of stiffness and impact resistance. Therefore, adding compatibilizer (B) to the mixed plastic blend (A) reduces the stiffness of the resulting polypropylene-polyethylene composition. However, the loss of stiffness is overcompensated by the improvement in impact resistance.

[0056] Preferably, the polypropylene-polyethylene composition according to the invention has a tensile modulus of 500 to 1400 MPa, more preferably 600 to 1350 MPa, and even more preferably 650 to 1300 MPa, measured at 23°C according to ISO 527-2.

[0057] Furthermore, the polypropylene-polyethylene composition preferably has a tensile modulus of 1750 to 4500 MPa, more preferably 2000 to 4250 MPa, and even more preferably 2250 to 4000 MPa, measured at -30°C according to ISO 527-2.

[0058] Furthermore, the polypropylene-polyethylene composition preferably has a yield stress of 12.5 to 50.0 MPa, more preferably 15.0 to 40.0 MPa, and even more preferably 16.5 to 30.0 MPa, as determined according to ISO 527-2 at 23°C.

[0059] Furthermore, the polypropylene-polyethylene composition preferably has a yield stress of 30.0 to 70.0 MPa, more preferably 35.0 to 60.0 MPa, and even more preferably 40 to 50.0 MPa, as determined according to ISO 527-2 at -30°C.

[0060] In addition, the polypropylene-polyethylene composition preferably has a fracture strain of 14.0 to 600.0%, more preferably 15.0 to 550.0%, and even more preferably 16.0 to 500.0% as measured according to ISO 527-2 at 23°C.

[0061] Furthermore, the polypropylene-polyethylene composition preferably has a fracture strain of 2.5 to 35.0%, more preferably 3.0 to 30.0%, and even more preferably 4.0 to 25.0% as determined by ISO 527-2 at -30°C.

[0062] Furthermore, the polypropylene-polyethylene composition preferably has a concentration of 5.0 to 50.0 kJ / m³. 2 More preferably 6.0 to 40.0 kJ / m 2 More preferably 6.5 to 30.0 kJ / m 2 Notched impact strength of a simply supported beam, measured at 23°C according to ISO 179.

[0063] Furthermore, the polypropylene-polyethylene composition preferably has a concentration of 1.0 to 15.0 kJ / m³. 2 More preferably 2.0 to 12.5 kJ / m 2 More preferably, 2.5 to 10.0 kJ / m 2 Notched impact strength of a simply supported beam, measured at -20°C according to ISO 179.

[0064] Furthermore, the polypropylene-polyethylene composition preferably has a concentration of 1.0 to 15.0 kJ / m³. 2 More preferably 2.0 to 12.5 kJ / m 2 More preferably, 2.5 to 10.0 kJ / m 2 Notched impact strength of a simply supported beam, measured at -30°C according to ISO 179.

[0065] Furthermore, the polypropylene-polyethylene composition preferably has a puncture energy of 8.5 to 35.0 J, more preferably 10.0 to 30.0 J, and even more preferably 12.0 to 25.0 J, as determined according to ISO 6603-2 at 23°C on a 2 mm thick specimen.

[0066] In addition, the polypropylene-polyethylene composition preferably has a puncture energy of 0.4 to 35.0 J, more preferably 0.5 to 30.0 J, and even more preferably 0.6 to 25.0 J, as determined according to ISO 6603-2 at -30°C on a 2 mm thick specimen.

[0067] Preferably, the polypropylene-polyethylene composition has a strength of 4750 to 40000 MPa·kJ / m³. 2 Preferably 5000 to 35000 MPa·kJ / m 2 More preferably 5100 to 30000 MPa·kJ / m 2 The impact-stiffness (IS) balance is the product of the impact strength of a simply supported beam and the tensile modulus, wherein the tensile modulus is determined according to ISO 527-2 at 23°C, and the impact strength of the simply supported beam is determined according to ISO 179 at 23°C.

[0068] Furthermore, the polypropylene-polyethylene composition preferably has a puncture energy-stiffness (PS) balance of 9750 to 30000 MPa·J, more preferably 10000 to 27500 MPa·J, and even more preferably 10500 to 25000 MPa·J, which is the product of puncture energy and tensile modulus, wherein the puncture energy is determined according to ISO 6603-2 at 23°C on a specimen with a thickness of 2 mm, and the tensile modulus is determined according to ISO 527-2 at 23°C.

[0069] Furthermore, the polypropylene-polyethylene composition preferably has an impact-stiffness (IS-1) balance of 750 to 3000, more preferably 800 to 2750, and even more preferably 850 to 2650, calculated according to the following formula in relation to the weight of the compatibilizer (B):

[0070]

[0071] in:

[0072] IS-1 represents the impact-stiffness balance related to the weight of compatibilizer (B), expressed as [(MPa·kJ) / (wt.-%·m]. 2 )]count;

[0073] The NIS of a simply supported beam is the notched impact strength of a simply supported beam measured at 23°C according to ISO 179, expressed in kJ / m. 2 count;

[0074] TM is the tensile modulus measured at 23°C according to ISO 527-2, in MPa; and

[0075] Weight % (B) is the weight of compatibilizer (B) in the polypropylene-polyethylene composition, expressed as a percentage by weight.

[0076] Furthermore, the polypropylene-polyethylene composition preferably has a first puncture energy-stiffness (PS-1) balance of 500 to 7500, more preferably 600 to 7000, and even more preferably 750 to 6000, calculated according to the following formula in relation to the weight of the compatibilizer (B):

[0077]

[0078] in:

[0079] PS-1 is the first puncture energy-stiffness balance related to the weight of compatibilizer (B), expressed as [(MPa·J) / wt.-%];

[0080] PE (23°C) is the puncture energy, expressed in J, measured at 23°C on a 2 mm thick specimen according to ISO 6603-2.

[0081] TM is the tensile modulus measured at 23°C according to ISO 527-2, in MPa; and

[0082] Weight % (B) is the weight of compatibilizer (B) in the polypropylene-polyethylene composition, expressed as a percentage by weight.

[0083] Furthermore, the polypropylene-polyethylene composition preferably has a second puncture energy-stiffness (PS-2) balance related to the weight of the compatibilizer (B), calculated according to the following formula, of 40 to 1200, more preferably 50 to 1100, and even more preferably 60 to 1000:

[0084]

[0085] in:

[0086] PS-2 is the second puncture energy-stiffness balance related to the weight of compatibilizer (B), expressed as [(MPa·J) / wt.-%];

[0087] PE (-30℃) is the puncture energy, expressed in J, measured at -30℃ on a 2 mm thick specimen according to ISO 6603-2.

[0088] TM is the tensile modulus measured at 23°C according to ISO 527-2, in MPa; and

[0089] Weight % (B) is the weight of compatibilizer (B) in the polypropylene-polyethylene composition, expressed as a percentage by weight.

[0090] The polypropylene-polyethylene composition is preferably obtained by mixing a plastic blend (A), a compatibilizer (B), and optionally a stabilizer or a mixture of stabilizers; more preferably by blending a plastic blend (A), a compatibilizer (B), and optionally a stabilizer or a mixture of stabilizers; and most preferably by melt blending a plastic blend (A), a compatibilizer (B), and optionally a stabilizer or a mixture of stabilizers.

[0091] The blended plastics (A), compatibilizer (B), and optional stabilizer will be described in more detail below.

[0092] Mixed plastic blends (A)

[0093] The polypropylene-polyethylene composition includes a blend of plastics (A).

[0094] Blended plastic blends (A) are typically recycled materials based on a mixture of polypropylene and polyethylene.

[0095] The weight ratio of polypropylene to polyethylene in the mixed plastic blend (A) is 3:7 to 49:1, preferably 4:6 to 49:1, and more preferably 5:5 to 49:1.

[0096] Preferably, the recycled material is obtained from recycled waste using plastic recycling methods known in the art. Such recyclables are commercially available, for example, from Corepla (an Italian consortium responsible for the collection, recycling, and reuse of packaging plastic waste), Resource Plastics Corp. (Brampton, ON, Canada), Kruschitz GmbH, Plastics and Recycling (Austria), Vogt Plastik GmbH (Germany), Mtm ​​Plastics GmbH (Germany), Borealis AG (Austria), and others. Non-exhaustive examples of polypropylene-rich recycled materials include Dipolen. ® S, Dipolen ® PP and Purpolen ® PP (Mtm Plastics GmbH), Axpoly® recycled polypropylene granules (Axion Ltd), and PolyPropylene Copolymer (BSP Compounds).

[0097] During recycling, any reasonable measures are typically taken to reduce / remove any components other than polyethylene and polypropylene, provided that such measures are recommended for the end application or use; however, other components are often present in small amounts.

[0098] Other components of this type include polystyrene (PS), polyamide (PA), and polyethylene terephthalate (PET), all of which are present in the lowest possible amounts, preferably below the detection limit.

[0099] The mixed plastic blend (A) preferably has a melt flow rate MFR2, measured according to ISO 1133 at 230°C and 2.16 kg, in the range of 1.0 to 30.0 g / 10 min, more preferably in the range of 2.5 to 25.0 g / 10 min.

[0100] Furthermore, the mixed plastic blend (A) preferably has a concentration of 905 to 955 kg / m³. 3 More preferably 905 to 952 kg / m 3 Even more preferred is 905 to 950 kg / m³ 3 The density is determined according to ISO 1183.

[0101] The mixed plastic blend (A) can be characterized using trichlorobenzene (TCB) as a solvent via crystallization extraction (CRYSTEX). This method is described in the determination method section below. The crystalline fraction (CF) contains the majority of the matrix phase and only a small portion of the elastomer phase, while the soluble fraction (SF) contains the majority of the elastomer phase and only a small portion of the matrix phase. In some cases, this method yields more useful data than xylene extraction because the crystalline fraction (CF) and soluble fraction (SF) correspond more accurately to the matrix and elastomer phases, respectively. Because xylene extraction and crystallization extraction (CRYSTEX) are different separation methods, the properties of the XCS / XCI fraction are not entirely the same as those of the crystalline fraction / soluble fraction (CF / SF), meaning that the amounts and properties of the matrix and elastomer phases can differ.

[0102] Typically, the content of the crystalline fraction (CF) and the soluble fraction (SF) of a composition is only related to its polymeric components, i.e., there are no other components that are insoluble and therefore not part of the dissolution and crystallization cycle described below in the determination method.

[0103] In this invention, the mixed plastic blend (A) is typically completely soluble in trichlorobenzene (TCB), such that the content of the crystalline fraction (CF) and the content of the soluble fraction (SF) are related to the total content of the mixed plastic blend (A). Therefore, the content of the crystalline fraction (CF) and the content of the soluble fraction (SF) preferably account for 100% by weight of the mixed plastic blend (A).

[0104] In crystallization extraction (CRYSTEX) analysis, the mixed plastic blend (A) preferably exhibits one or all of the following properties:

[0105] - The content of crystalline fraction (CF) determined by crystallization extraction (CRYSTEX) based on the total weight of the mixed plastic blend (A), in the range of 80.0 to 96.0% by weight, preferably in the range of 82.5 to 95.5% by weight, and more preferably in the range of 85.0 to 95.0% by weight; and

[0106] - The content of soluble fraction (SF) determined by crystallization extraction (CRYSTEX) based on the total weight of the mixed plastic blend (A), in the range of 4.0 to 20.0% by weight, preferably in the range of 4.5 to 17.5% by weight, and more preferably in the range of 5.0 to 15.0% by weight.

[0107] The crystal fraction (CF) preferably has one or more of the following properties, and preferably all of the following properties:

[0108] - In the range of 2.5 to 55.0% by weight, preferably in the range of 3.5 to 52.5% by weight, and more preferably in the range of 5.0 to 50.0% by weight, by quantitative... 13 Ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy; and / or

[0109] - Intrinsic viscosity (iV(CF)) in decahydronaphthalene measured at 135°C according to DIN ISO 1628 / 1, less than 2.5 dl / g, preferably in the range of 1.1 to 2.3 dl / g, more preferably in the range of 1.4 to 2.1 dl / g.

[0110] The soluble fraction (SF) preferably has one or more of the following properties, and preferably all of the following properties:

[0111] - The content of the product is within the range of 20.0 to 55.0% by weight, preferably within the range of 22.0 to 52.5% by weight, and more preferably within the range of 24.0 to 50.0% by weight, by quantitative... 13 Ethylene content (C2(SF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy; and / or

[0112] - Intrinsic viscosity (iV(SF)) in decahydronaphthalene measured at 135°C according to DIN ISO 1628 / 1 in the range of 0.9 to 2.1 dl / g, preferably in the range of 1.0 to 2.0 dl / g, more preferably in the range of 1.1 to 1.9 dl / g.

[0113] The mixed plastic blend (A) preferably has a relative amount of ethylene-derived units of 3.5 to 60.0% by weight, more preferably 4.5 to 55.0% by weight, and more preferably 5.0 to 50.0% by weight, based on the total weight of the mixed plastic blend (A).

[0114] The mixed plastic blend (A) preferably has an inorganic residue content determined by calcination analysis according to DIN ISO 1172:1996, ranging from 0.05 to 3.0% by weight, more preferably from 0.5 to 2.5% by weight, and most preferably from 1.0 to 2.5% by weight.

[0115] The blended plastics (A) is preferably derived from post-industrial or post-consumer waste, with post-consumer waste being the most preferred source. This means that the blend (A) is recycled from waste plastic materials.

[0116] The mixed plastic blend (A) preferably has a limonene content determined by solid phase microextraction (HS-SPME-GC-MS) in the range of 0.1 to 100 ppm, more preferably in the range of 0.1 to 50 ppm, and even more preferably in the range of 0.1 to 35 ppm.

[0117] The presence of limonene indicates that the mixed plastic blend (A) originated from post-consumer waste.

[0118] Further indications of the recyclability of the mixed plastic blend (A) include the presence of other polymers, such as polystyrene and polyamide-6, as well as the presence of fatty acids.

[0119] Therefore, it is further preferred that the mixed plastic blend (A) includes one or more of polystyrene, polyamide-6 and fatty acids, preferably each of polystyrene, polyamide-6 and fatty acids.

[0120] The mixed plastic blend (A) preferably has a tensile modulus of 600 MPa to 1500 MPa, more preferably 650 MPa to 1400 MPa, and even more preferably 700 MPa to 1300 MPa, measured at 23°C according to ISO 527-2.

[0121] Furthermore, the mixed plastic blend (A) preferably has a concentration of 2.5 to 10.0 kJ / m³. 2 More preferably 3.5 to 9.0 kJ / m 2 Even more preferred is 4.0 to 8.0 kJ / m 2 Notched impact strength of a simply supported beam at 23°C, as determined according to ISO 179 (CNIS at 23°C).

[0122] Before blending with other components used to prepare the polypropylene-polyethylene composition, the blended plastic blend (A) can be aerated, for example as described in EP 3 786 190 A1, to remove volatile components.

[0123] Compatibilizer (B)

[0124] The polypropylene-polyethylene composition further includes a compatibilizer (B).

[0125] Compatibilizer (B) is a C2C4 plastic.

[0126] C2C4 plastomer is a plastomer copolymer containing ethylene monomer and 1-butene comonomer, which has both elastomer and plastic properties.

[0127] Therefore, it is preferable that the 1-butene comonomer is incorporated into the C2C4 plastic body in a random form, so that the C2C4 plastic body is a random copolymer of ethylene and 1-butene.

[0128] Random copolymers are different from block copolymers that have ethylene-rich blocks and 1-butene-rich blocks in the polymer chain.

[0129] The compatibilizer (B) is preferably the original polymer, which is mixed with the other components in the polypropylene-polyethylene composition according to the invention.

[0130] Residual C2C4 plasmons that may be present in the mixed plastic blend (A) are not classified as compatibilizers (B).

[0131] Compatibilizer (B) has a melt flow rate (MFR2) measured according to ISO 1133 at 190°C and 2.16 kg in the range of 0.1 to 5.0 g / 10 min, preferably in the range of 0.1 to 3.5 g / 10 min, and more preferably in the range of 0.1 to 2.5 g / 10 min.

[0132] In addition, compatibilizer (B) has a strength of 850 to 885 kg / m³. 3 Preferred weight is 855 to 875 kg / m³. 3 More preferably 860 to 870 kg / m 3 The density is determined according to ISO 1183.

[0133] In addition, the compatibilizer (B) has a melting temperature Tm of less than 65°C, preferably 25 to 45°C, more preferably 30 to 40°C, as determined by DSC according to ISO 11357.

[0134] Furthermore, the compatibilizer (B) preferably has a glass transition temperature Tg of -40 to -75°C, more preferably -45 to -70°C, and more preferably -50 to -65°C, as determined by DSC according to ISO 11357.

[0135] C2C4 plastics are typically polymerized in solution in the presence of metallocene catalysts. Suitable metallocene catalysts and polymerization conditions for the production of C2C4 plastics are well known in the art.

[0136] C2C4 plastomers suitable as compatibilizers (B) are also commercially available, for example from DOW Chemical Corp (USA) under the trade name Engage®.

[0137] (one or more) stabilizers

[0138] The polypropylene-polyethylene composition of the present invention may contain up to 1.0% by weight of a stabilizer or a mixture of stabilizers. Preferably, the stabilizer is contained in an amount of 0.1 to 1.0% by weight based on the total weight of the polypropylene-polyethylene composition.

[0139] Stabilizers are well known in the art and can be, for example, antioxidants, anti-acids, anti-caking agents, UV stabilizers, nucleating agents, or antistatic agents.

[0140] Examples of commonly used antioxidants in this field include: sterically hindered phenols (e.g., CAS number 6683-19-8, also used as Irganox 1010 FF). TM Sold by BASF); phosphorus-based antioxidants (e.g., CAS No. 31570-04-4, also available as Hostanox PAR 24 (FF)). TM Sold by Clariant, or as Irgafos 168 (FF) TM Sold by BASF); sulfur-based antioxidants (e.g., CAS No. 693-36-7, as Irganox PS-802 FL) TM Sold by BASF); nitrogen-based antioxidants (e.g., 4,4'-bis(1,1'-dimethylbenzyl)diphenylamine); or antioxidant blends.

[0141] Antioxidants are also well known in the art. Examples include calcium stearate, sodium stearate, zinc stearate, magnesium and zinc oxides, synthetic hydrotalcites (e.g., SHT, CAS No. 11097-59-9), lactates and lactylates, as well as calcium stearate (CAS No. 1592-23-0) and zinc stearate (CAS No. 557-05-1).

[0142] Common anti-caking agents include: natural silica, such as diatomaceous earth (e.g., CAS No. 60676-86-0 (SuperfFloss)). TM ), CAS number 60676-86-0 (SuperFloss E TM ) or CAS number 60676-86-0 (Celite499) TM Synthetic silica (e.g., CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 112926-00-8, CAS No. 7631-86-9 or CAS No. 7631-86-9); silicates (e.g., aluminum silicate (kaolin), CAS No. 112926-00-8, CAS No. 7631-86-9 or CAS No. 7631-86-9); CAS No. 1318-74-7; Sodium aluminum silicate, CAS No. 1344-00-9; Calcined kaolin, CAS No. 92704-41-1; Aluminum silicate, CAS No. 1327-36-2; or calcium silicate, CAS No. 1344-95-2; Synthetic zeolites (e.g., sodium calcium aluminosilicate hydrate, CAS No. 1344-01-0; CAS No. 1344-01-0; or calcium sodium aluminosilicate hydrate, CAS No. 1344-01-0).

[0143] Examples of UV stabilizers include bis(2,2,6,6-tetramethyl-4-piperidinyl)-sebate (CAS No. 52829-07-9, Tinuvin 770); and 2-hydroxy-4-n-octyloxybenzophenone (CAS No. 1843-05-6, Chimassorb 81).

[0144] Nucleating agents include, for example, sodium benzoate (CAS No. 532-32-1); 1,3:2,4-bis(3,4-dimethylbenzyl)sorbitol (CAS 135861-56-2, Millad 3988).

[0145] Suitable antistatic agents include, for example, glycerides (CAS No. 97593-29-8), ethoxylated amines (CAS No. 71786-60-2 or 61791-31-9) or ethoxylated amides (CAS No. 204-393-1).

[0146] Typically, these stabilizers are added in amounts of 100 to 2,000 ppm for each individual component of the polymer.

[0147] Products

[0148] In another aspect, the present invention relates to articles comprising polypropylene-polyethylene compositions as described above or below.

[0149] Therefore, it is preferred that all aspects of the polypropylene-polyethylene composition and its components as described above or below are applicable to the articles.

[0150] The article may comprise a majority by weight of the polypropylene-polyethylene composition as described above or below, i.e., more than 50% to 100% by weight of the article.

[0151] However, typically, before forming the article, the polypropylene-polyethylene composition as described above or below is melt-blended with other polymeric components (usually the original polymeric components) and non-polymeric components (e.g., additives, fillers, and pigments). Therefore, the amount of the polypropylene-polyethylene composition in the article is preferably in the range of 10% to 75% by weight of the article.

[0152] use

[0153] On the other hand, the present invention relates to the use of compatibilizer (B) in polypropylene-polyethylene compositions as described above or below for increasing the puncture energy-stiffness (PS) balance of the polypropylene-polyethylene composition to a range of 125% to 500%, preferably 150% to 300%, of the puncture energy-stiffness (PS) balance of the blend (A).

[0154] The puncture energy-stiffness (PS) balance is the product of the puncture energy measured at 23°C on a 2 mm thick specimen according to ISO 6603-2 and the tensile modulus measured at 23°C according to ISO 527-2.

[0155] Therefore, it is preferred that all aspects of the polypropylene-polyethylene composition and its components as described above or below are suitable for the application.

[0156] The invention will now be described in more detail through the examples provided below.

[0157] Example

[0158] The following examples are included to illustrate certain aspects and embodiments of the invention as described in the claims. However, those skilled in the art will understand that the following description is merely illustrative and should not be construed as limiting the invention in any way.

[0159] A. Measurement Method

[0160] Unless otherwise defined, the following definitions of terms and measurement methods apply to the above general description of the invention and the following examples.

[0161] melt flow rate

[0162] Melt flow rate (MFR) is determined according to ISO 1133 and expressed in g / 10 min. MFR indicates the flowability of a polymer and therefore its processability. The higher the melt flow rate, the lower the viscosity of the polymer.

[0163] The MFR2 of polypropylene was determined at a temperature of 230°C and a load of 2.16 kg.

[0164] The MFR2 of polyethylene was determined at a temperature of 190°C and a load of 2.16 kg.

[0165] Determination of the contents of isotactic polypropylene (iPP), polystyrene (PS), ethylene and polyamide-6

[0166] Calibration standards were prepared by blending iPP and HDPE to establish calibration curves. The thickness of the calibration standard film was 300 μm. To quantify the iPP, PS, and PA6 content in the samples, quantitative IR spectra were recorded in solid state using a Bruker Vertex 70 FTIR spectrometer. Spectra were recorded on 25 × 25 mm square films with a thickness of 50 to 100 μm, prepared by compression molding at 190 °C and 4 to 6 mPa. A standard transmission FTIR spectrometer was used, with a wavelength of 4000 to 400 cm⁻¹. -1 Spectral range, 6 mm aperture, 2 cm -1 Spectral resolution, 16 background scans, 16 spectral scans, 32 interferogram zero fill factor and Norton Beer strong apodization.

[0167] iPP measured at 1167 cm -1 Absorption at specific wavelengths was measured, and the iPP content was quantified based on the calibration curve (absorption / thickness (in cm) relative to iPP content (in weight %)).

[0168] Measured at 1601 cm -1 (PS) and 3300 cm -1 Absorption at the (PA6) band was measured, and the PS and PA6 contents were quantified according to the calibration curve (absorption / thickness (in cm) relative to PS and PA contents (in wt%)). Ethylene content was obtained by subtracting iPP, PS, and PA6 from 100. The analysis was performed using a dual determination method.

[0169] References

[0170] [1] Van Gemert LJ, Odour Thresholds: Compilations of odourthreshold values ​​in air, water and other media, Utrecht, Oliemans Punter &Partners BV, 2011.

[0171] The crystallization fraction and soluble fraction, along with their respective properties (IV and ethylene content), were determined by crystallization extraction (CRYSTEX).

[0172] The crystalline fraction (CF) and soluble fraction (SF) of polypropylene (PP) compositions, along with the comonomer content and intrinsic viscosity of the corresponding fractions, were analyzed using the Crystex (crystallization extraction) method. Potential instruments that can be used include the Crystex QC or Crystex 42 (Polymer Char; Valencia, Spain). Details of this technique and method can be found in the literature (Ljiljana Jeremic, Andreas Albrecht, Martina Sandholzer & Markus Gahleitner (2020): Rapid characterization of high-impact ethylene–propylene copolymer composition by crystallization extraction separation: comparability to standard separation methods, International Journal of Polymer Analysis and Characterization, 25:8, pp. 581-596).

[0173] The crystalline and amorphous fractions were separated by temperature cycling of dissolution at 160 °C, crystallization at 40 °C, and redissolution in 1,2,4-trichlorobenzene at 160 °C. Quantification of SF and CF, as well as determination of ethylene content (C2), were achieved using an integrated infrared detector (IR4), and intrinsic viscosity (IV) was determined using an online 2-capillary viscometer.

[0174] The IR4 detector operates in two different wavelength bands (CH3 stretching vibration (center at approximately 2960 cm)). -1 (at location) and CH stretching vibration (2700 to 3000 cm) -1A multi-wavelength detector is used to measure IR absorbance at two different wavelengths. The IR absorbance at these two different wavelengths is used to determine the concentration and ethylene content in ethylene-propylene copolymers. The IR4 detector is calibrated with a series of eight EP copolymers having known ethylene contents ranging from 2% to 69% by weight (via...). 13 (Determined by C-NMR spectroscopy), and each EP copolymer had multiple concentrations in the range of 2 and 13 mg / ml. To simultaneously capture both characteristics of the various polymer concentrations expected during Crystex analysis, concentration and ethylene content, the following calibration equation was applied:

[0175] Concentration = a + b * absorbance (CH) + c * (absorbance (CH)) 2 + d*Absorbance (CH3) + e*Absorbance (CH3) 2 + f*Absorbance (CH)*Absorbance (CH3) (Equation 1)

[0176] CH3 / 1000C = a + b * absorbance (CH) + c * absorbance (CH3) + d * (absorbance (CH3) / absorbance (CH)) + e * (absorbance (CH3) / absorbance (CH)) 2 (Equation 2)

[0177] The constants a to f used in Equation 1 and the constants a to e used in Equation 2 were determined using least squares regression analysis.

[0178] Use the following relationship to convert CH3 / 1000C to ethylene content in weight percent:

[0179] Weight % (ethylene in EP copolymer) = 100 - CH3 / 1000TC * 0.3 (Equation 3)

[0180] The amounts of soluble fraction (SF) and crystalline fraction (CF) were correlated, respectively, with the amounts of "cold soluble xylene" (XCS) and cold insoluble xylene (XCI) fractions determined according to standard gravimetric analysis in accordance with ISO 16152 via XS calibration. XS calibration was achieved by testing various EP copolymers with XS contents ranging from 2% to 31% by weight. Linear calibration curves were used.

[0181] The intrinsic viscosity (IV) of the parent EP copolymer and its soluble and crystalline fractions was determined using an online 2-capillary viscometer and correlated with the corresponding IV determined in decahydronaphthalene according to standard methods in ISO 1628-3. Calibration was performed using various EP copolymers and PP polymers with IVs ranging from 2 to 4 dl / g. The determined calibration curves were linear.

[0182] Weigh out the sample to be analyzed at a concentration of 10 mg / ml to 20 mg / ml.

[0183] After autofilling vials with 1,2,4-TCB containing 250 mg / L of 2,6-tert-butyl-4-methylphenol (BHT) as an antioxidant, the sample was dissolved at 170°C until complete dissolution was achieved with continuous stirring or gentle agitation. To prevent sample degradation, the polymer solution was covered with a nitrogen atmosphere during dissolution.

[0184] For PP compositions containing inorganic fillers, pigments, or any other non-TCB-soluble polymeric substances, these substances need to be removed. This can be done by thermal filtration before injection.

[0185] A defined volume of polymer solution was injected into a column packed with an inert support, where crystallization of the sample and separation of the soluble fraction from the crystalline fraction were performed. This process was repeated twice. During the first injection, the entire sample was measured at high temperature, and the IV [dl / g] and C2 [wt%] of the PP composition were determined. During the second injection, the soluble fraction (at low temperature) and the crystalline fraction (at high temperature) were measured using a crystallization cycle (wt% SF, wt% C2, IV).

[0186] Intrinsic viscosity

[0187] Intrinsic viscosity (iV) was measured according to DIN ISO 1628 / 1, October 1999 (at 135°C in decahydronaphthalene).

[0188] density:

[0189] Density was measured according to ISO 1183-187. Sample preparation was carried out by compression molding according to ISO 1872-2:2007.

[0190] DSC analysis, melting temperature (T) m ), heat of fusion (H) f ), crystallization temperature (T) c ), heat of crystallization (H) c ) and glass-rubber transition temperature (Tg)

[0191] Samples ranging from 5 to 7 mg were measured using a TA Instrument Q200 differential scanning calorimeter (DSC). The DSC was operated according to ISO 11357 / Part 3 / Method C2 in a heating / cooling / heating cycle at a temperature range of -30 to +225 °C and a scan rate of 10 °C / min. Crystallization temperature (T... c ) and enthalpy of crystallization (H cThe melting temperature (T) is determined by the cooling step, while the melting temperature (T) is determined by the melting step. m ) and enthalpy of fusion (H m The temperature gradient (Tg) was determined by the second heating step. Tg was evaluated as the inflection point of reversible heat flow in the temperature modulation experiment. The sample was heated from -85°C at a rate of 2°C / min, with modulation of 0.32°C every 60 seconds.

[0192] Notched impact strength of simply supported beam

[0193] Notched impact strength (NIS) of simply supported beams was measured according to ISO 179 1eA at +23°C, -20°C, or -30°C, using 80×10×4 mm beams prepared according to ISO 19069-2. 3 For the injection-molded rod test specimens, a melt temperature of 230°C was used for all materials, regardless of the material melt flow rate.

[0194] Tensile properties

[0195] Tensile properties (tensile modulus, tensile strength, tensile strain at strength, tensile stress at break, tensile strain at break) are determined according to ISO 527-2 Method B on dog-bone specimens (1A ISO 527-2 or 1B ISO 527-2). According to this standard, the tensile modulus is tested at a speed of 1 mm / min, and all other properties are tested at a speed of 50 mm / min. The test temperature is +23±2℃ or -30±2℃. Injection molding or compression molding is performed according to ISO 19069-2.

[0196] Instrumented puncture test - puncture energy

[0197] Maximum force, deflection at maximum force, energy to reach maximum force, puncture deflection, and puncture energy were determined according to ISO 6603-2 in the instrumented puncture impact behavior test. The specimens were injection-molded sheets (according to ISO 19069-2, for PP) cut to dimensions of 60 mm × 60 mm × 2 mm. The test conditions were: impact velocity of 4.4 m / s, a lubricated punch with a diameter of 20 mm, at 23 ± 2 °C. The specimens were clamped with a support ring with a diameter of 40 mm.

[0198] Limonene detection

[0199] The determination of limonene was based on a static headspace (HS) method. This analysis used an HS injector in combination with a gas chromatograph (GC) and a mass spectrometer (MS) for screening purposes.

[0200] Samples were delivered to the laboratory in sealed aluminum-coated polyethylene (PE) bags. Prior to analysis, the samples were cold-ground, and a portion of 2.000 ± 0.100 g was weighed and placed in a 20 ml HS vial, which was then tightly sealed. Each sample was analyzed twice.

[0201] HS / GC / MS parameters

[0202] • HS parameters (Agilent G1888 headspace sampler)

[0203] Vial equilibration time: 120 min (samples), 5 min (standards)

[0204] Oven temperature: 100℃ (samples), 200℃ (standards)

[0205] Loop temperature: 110℃ (sample), 205℃ (standard)

[0206] Transmission line temperature: 120℃ (sample), 210℃ (standard)

[0207] low oscillation

[0208] • GC parameters (Agilent 7890A GC system)

[0209] Column: ZB-WAX 7HG-G007-22 (30 m×250 µm×1 µm)

[0210] Carrier gas: Helium 5.0

[0211] Flow rate: 2 ml / min

[0212] Split ratio: 5:1

[0213] GC oven program: 35℃, 0.1 min

[0214] 10℃ / min until 250℃

[0215] 250℃ for 1 minute

[0216] • MS Specifications (Agilent 5975C Inert XL MSD)

[0217] Acquisition mode: Scan

[0218] Scan parameters:

[0219] Low quality: 20

[0220] High quality: 200

[0221] Threshold: 10

[0222] • Software / Data Evaluation

[0223] MSD ChemStation E.02.02.1431

[0224] MassHunter GC / MS Acquisition B.07.05.2479

[0225] AMDIS GC / MS Analysis Version 2.71

[0226] NIST / EPA / NIH mass spectrometry library (2011 version)

[0227] NIST mass spectrometry search program Version 2.0 g

[0228] • AMDIS deconvolution parameters

[0229] Minimum matching factor: 80

[0230] Threshold: Low

[0231] Scanning direction: from high to low

[0232] Data file format: Agilent file

[0233] Instrument type: Quadrupole

[0234] Component width: 20

[0235] Adjacent peak subtraction: two

[0236] Resolution: High

[0237] Sensitivity: Very high

[0238] Shape requirement: Medium

[0239] Solvent tailing: 91 m / z

[0240] Column loss: 207 m / z

[0241] Minimum model peak: 2

[0242] Minimum S / N: 10

[0243] Minimum definite peak: 0.5

[0244] • MSD ChemStation integral parameters

[0245] Integrator: ChemStation

[0246] Initial area rejection: 0

[0247] Initial peak width: 0.005

[0248] Shoulder peak detection: Off

[0249] Initial threshold: 10.5

[0250] In this study, the statement "below the limit of detection (<LOD)" describes the situation where the match factor is lower than 80 (AMDIS), or the signal-to-noise ratio of the peak in the sample run (Pk-pk S / N = corrected signal / Pk-pk noise, MSD ChemStation signal-to-noise ratio report) is lower than 3. The results only relate to the measured samples, measurement time and applied parameters.

[0251] standard solutions

[0252] For positive identification and comparison with the (minimum) odor detection threshold (ODT), a limonene standard was used.

[0253] For HS / GC / MS analysis, 5 µl of the corresponding standard was injected into a 20 ml HS vial, which was tightly sealed and then measured.

[0254] Assuming the standard substance is completely vaporized, the concentration of limonene in the HS is estimated as listed in Fehler! Verweisquelle konnte nicht gefunden werden..

[0255] Table 1: Calibration standards and ODT

[0256]

[0257] Data Evaluation

[0258] The concentration of the analyte in the HS is calculated by considering the amount of substance and the available HS volume (Equation 1).

[0259] Equation 1

[0260] To estimate the concentration of the analyte in the HS above the polymer sample, the response factor Rf from single-point calibration is required (Equation 2). The peak area of the analyte is obtained by integrating the extracted ion chromatogram (EIC). The corresponding target ions are listed in Fehler! Verweisquelle konnte nicht gefunden werden..

[0261] Equation 2

[0262] Concentration of analyte in HS above polymer sample It is calculated by multiplying the response factor by the area of ​​the EIC peak of the sample (Equation 3).

[0263] Equation 3

[0264] Furthermore, the odor relevance of the analytes in the HS above the polymer sample was estimated using odor activity values ​​(OAV). Therefore, the concentration of the analytes in the HS above the polymer sample was... Compare with the (lowest) odor detection threshold (ODT) found in the literature (Equation 4) [1]. Values ​​greater than 1 indicate that the analyte is odor-related at a given HS temperature.

[0265] Equation 4

[0266] Factors to consider and limitations

[0267] It must be considered that the ODT of some substances is below the detection limit (LOD) of this method. Therefore, components below the LOD may be missed, even though they are still relevant to the overall odor.

[0268] OAV is based on the assumption that the HS parameter is related to the measurement conditions of the ODT assay to some extent. Of course, this is not entirely applicable, as a temperature setting of 100°C is not necessarily chosen for such experiments, thus limiting its practical value. Nevertheless, this method can at least indicate the odor correlation of the defined labeled substance.

[0269] References

[0270] [1] Van Gemert LJ, Odour Thresholds: Compilations of odourthreshold values ​​in air, water and other media, Utrecht, Oliemans Punter &Partners BV, 2011.

[0271] 2. Example

[0272] Mixed plastic blends (A)

[0273] Table 1 shows the properties of the polypropylene / polyethylene blends A-1 and A-2 used for evaluation.

[0274] Table 1: Properties of polypropylene / polyethylene blends (blends A-1 and A-2)

[0275]

[0276] Compatibilizer (B)

[0277] As compatibilizer (B), the following commercially available ethylene-1-butene copolymer (C2C4 plastic) is used:

[0278] B-1: An ethylene-co-1-butene polymer with a density of 862 kg / m³ 3 The melt flow rate (MFR2, 190℃, ISO 1133) is 1.2 g / 10 min, and the melting temperature (Tm) is 34℃, making it suitable as an Engagement material. TM 7467 was purchased from Dow.

[0279] B-2: An ethylene-co-1-butene polymer with a density of 860 kg / m³ 3 The melt flow rate (MFR2, 190℃, ISO 1133) is <0.5 g / 10 min, and the melting temperature (Tm) is 37℃, making it suitable as an Engagement Container. TM 7487 was purchased from Dow.

[0280] Preparation of polypropylene-polyethylene compositions

[0281] The blend (A) and compatibilizer (B) were melt-blended on a co-rotating twin-screw extruder in the amounts shown in Table 2 below.

[0282] Table 2: Composition of the embodiments and comparative examples of the present invention

[0283]

[0284] The properties of the comparative composition and the composition of the present invention are summarized in Table 3.

[0285] Table 3: Properties of CE1, CE2, and IE1 to IE8

[0286]

[0287] nm = Not measured

[0288] na = Not applicable

[0289] IS equilibrium = Impact strength of a simply supported beam at 23℃ multiplied by tensile modulus at 23℃

[0290] PS equilibrium = puncture energy at 23℃ multiplied by tensile modulus at 23℃

[0291]

[0292]

[0293]

[0294] As expected, by adding compatibilizer (B) to blend (A), the stiffness of the resulting composition (measured by tensile modulus) decreased, while the impact performance (measured by simply supported beam NIS and puncture energy) increased.

[0295] Surprisingly, however, as can be seen by comparing the balances of IS, PS, IS-1, PS-1, and PS-2, the loss of stiffness is overcompensated by the improvement in impact performance.

Claims

1. A polypropylene-polyethylene composition comprising: a) 75 to 99% by weight, preferably 77 to 98% by weight, more preferably 75 to 95% by weight of a mixed plastic blend (A), said mixed plastic blend (A) comprising: A-1) Polypropylene, and A-2) Polyethylene, in, The weight ratio of polypropylene to polyethylene is 3:7 to 49:1, preferably 4:6 to 49:1, and more preferably 5:5 to 49:1; and b) 1 to 25% by weight, preferably 2 to 23% by weight, more preferably 5 to 20% by weight, of a compatibilizer (B), said compatibilizer (B) being a C2C4 plastic and having - A melting temperature Tm determined by DSC according to ISO 11357, below 65°C, preferably 25 to 45°C, more preferably 30 to 40°C; - A melt flow rate MFR2, measured according to ISO 1133 at a load of 2.16 kg and a temperature of 190°C, in an amount of 0.1 to 5.0 g / 10 min, preferably 0.1 to 3.5 g / 10 min, more preferably 0.1 to 2.5 g / 10 min; and - 850 to 885 kg / m 3 Preferred weight is 855 to 875 kg / m³. 3 More preferably 860 to 870 kg / m 3 The density as determined according to ISO 1183; c) 0 to 1.0% by weight of stabilizer or a mixture of stabilizers. All quantities are based on the total weight of the polypropylene-polyethylene composition. The polypropylene-polyethylene composition has a melt flow rate (MFR2) of 1.5 to 50.0 g / 10 min, preferably 1.7 to 35.0 g / 10 min, and more preferably 2.0 to 25.0 g / 10 min, as determined according to ISO 1133 at a load of 2.16 kg and a temperature of 230°C.

2. The polypropylene-polyethylene composition according to claim 1, wherein, Based on the total weight of the blend (A), the blend (A) has a relative amount of ethylene-derived units of 3.5 to 60.0% by weight, preferably 4.5 to 55.0% by weight, and more preferably 5.0 to 50.0% by weight.

3. The polypropylene-polyethylene composition according to claim 1 or 2, wherein, The blend (A) is recovered from waste plastic materials derived from post-consumer waste and / or industrial waste, preferably from post-consumer waste.

4. The polypropylene-polyethylene composition according to any one of claims 1 to 3, wherein, The blend (A) has a limonene content of 0.1 to 100 ppm, preferably 0.1 to 50 ppm, more preferably 0.1 to 35 ppm, as determined by solid-phase microextraction (HS-SPME-GC-MS).

5. The polypropylene-polyethylene composition according to any one of claims 1 to 4, wherein, The blend (A) has one or more of the following properties, or all of the following properties: - Tensile modulus measured at 23°C according to ISO 527-2, 600 to 1500 MPa, preferably 650 to 1400 MPa, more preferably 700 to 1300 MPa; and / or - 2.5 to 10.0 kJ / m 2 The preferred concentration is 3.5 to 9.0 kJ / m³. 2 More preferably 4.0 to 8.0 kJ / m 2 Notched impact strength of a simply supported beam, measured at 23°C according to ISO 179; and / or - 905 to 955 kg / m 3 Optimal weight is 905 to 952 kg / m³ 3 More preferably 905 to 950 kg / m 3 The density is determined according to ISO 1183.

6. The polypropylene-polyethylene composition according to any one of claims 1 to 5, wherein, The blend (A) has a crystalline fraction (CF) content determined by crystallization extraction (CRYSTEX) in the range of 80.0 to 96.0% by weight, preferably in the range of 82.5 to 95.5% by weight, more preferably in the range of 85.0 to 95.0% by weight, based on the total weight of the mixed plastic blend (A), and a soluble fraction (SF) content determined by crystallization extraction (CRYSTEX) in the range of 4.0 to 20.0% by weight, preferably in the range of 4.5 to 17.5% by weight, more preferably in the range of 5.0 to 15.0% by weight, based on the total weight of the mixed plastic blend (A). The crystal fraction (CF) preferably has: - The content of the substance is in the range of 2.5 to 55.0% by weight, preferably in the range of 3.5 to 52.5% by weight, and more preferably in the range of 5.0 to 50.0% by weight, by quantitative... 13 Ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy; and / or - Intrinsic viscosity (iV(CF)) in decahydronaphthalene measured at 135°C according to DIN ISO 1628 / 1, less than 2.5 dl / g, preferably in the range of 1.1 to 2.3 dl / g, more preferably in the range of 1.4 to 2.1 dl / g; The soluble fraction (SF) preferably has the following characteristics: - The content of the substance is within the range of 20.0 to 55.0% by weight, preferably within the range of 22.0 to 52.5% by weight, and more preferably within the range of 24.0 to 50.0% by weight, by quantitative... 13 Ethylene content (C2(SF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy; and / or - Intrinsic viscosity (iV(SF)) measured according to ISO 1628-3 in the range of 0.9 to 2.1 dl / g, preferably in the range of 1.0 to 2.0 dl / g, and more preferably in the range of 1.1 to 1.9 dl / g.

7. The polypropylene-polyethylene composition according to any one of claims 1 to 6, wherein, The compatibilizer (B) has a glass transition temperature Tg of -40 to -75°C, preferably -45 to -70°C, more preferably -50 to -65°C, as determined by DSC according to ISO 11357.

8. The polypropylene-polyethylene composition according to any one of claims 1 to 7, having one or more of the following properties, or having all of the following properties: - Tensile modulus measured at 23°C according to ISO 527-2, 500 to 1400 MPa, preferably 600 to 1350 MPa, more preferably 650 to 1300 MPa; - 5.0 to 50.0 kJ / m 2 Preferably 6.0 to 40.0 kJ / m 2 More preferably 6.5 to 30.0 kJ / m 2 Notched impact strength of a simply supported beam, measured at 23°C according to ISO 179; - Puncture energy of 8.5 to 35.0 J, preferably 10.0 to 30.0 J, more preferably 12.0 to 25.0 J, measured at 23°C on a 2 mm thick specimen according to ISO 6603-2; - Puncture energy of 0.4 to 35.0 J, preferably 0.5 to 30.0 J, more preferably 0.6 to 25.0 J, measured at -30°C on a 2 mm thick specimen according to ISO 6603-2.

9. The polypropylene-polyethylene composition according to any one of claims 1 to 8, having a strength of 4750 to 40000 MPa·kJ / m 2 Preferably 5000 to 35000 MPa·kJ / m 2 More preferably 5100 to 30000 MPa·kJ / m 2 The impact-stiffness (IS) balance is the product of the impact strength and tensile modulus of a simply supported beam, wherein... The tensile modulus was determined according to ISO 527-2 at 23°C, and the impact strength of the simply supported beam was determined according to ISO 179 at 23°C.

10. The polypropylene-polyethylene composition according to any one of claims 1 to 9, having a puncture energy-stiffness (PS) balance of 9750 to 30000 MPa·J, preferably 10000 to 27500 MPa·J, more preferably 10500 to 25000 MPa·J, wherein the puncture energy-stiffness (PS) balance is the product of puncture energy and tensile modulus, wherein... The puncture energy was determined according to ISO 6603-2 at 23°C on a specimen with a thickness of 2 mm, and the tensile modulus was determined according to ISO 527-2 at 23°C.

11. The polypropylene-polyethylene composition according to any one of claims 1 to 10, having an impact-stiffness (IS) balance of 750 to 3000, preferably 800 to 2750, more preferably 850 to 2650, in relation to the weight of the compatibilizer (B) calculated according to the following formula: in IS-1 is the impact-stiffness balance related to the weight of the compatibilizer (B), expressed as [(MPa·kJ) / (wt.-%·m]. 2 )]count; The NIS of a simply supported beam is the notched impact strength of a simply supported beam measured at 23°C according to ISO 179, expressed in kJ / m. 2 count; TM is the tensile modulus measured at 23°C according to ISO 527-2, in MPa; and The weight % (B) is the weight of the compatibilizer (B) in the polypropylene-polyethylene composition, expressed as a percentage by weight.

12. The polypropylene-polyethylene composition according to any one of claims 1 to 11, having a first puncture energy-stiffness (PS-1) balance of 500 to 7500, preferably 600 to 7000, more preferably 750 to 6000, calculated according to the following formula in relation to the weight of the compatibilizer (B): in PS-1 is the first puncture energy-stiffness balance related to the weight of the compatibilizer (B), expressed as [(MPa·J) / wt.-%]; PE (23°C) is the puncture energy, expressed in J, measured at 23°C on a 2 mm thick specimen according to ISO 6603-2. TM is the tensile modulus measured at 23°C according to ISO 527-2, in MPa; as well as The weight % (B) is the weight of the compatibilizer (B) in the polypropylene-polyethylene composition, expressed as a percentage by weight.

13. The polypropylene-polyethylene composition according to any one of claims 1 to 12, having a second puncture energy-stiffness (PS-2) balance of 40 to 1200, preferably 50 to 1100, more preferably 60 to 1000, in relation to the weight of the compatibilizer (B) calculated according to the following formula: in PS-2 is the second puncture energy-stiffness balance related to the weight of the compatibilizer (B), expressed as [(MPa·J) / wt.-%]; PE (-30℃) is the puncture energy, expressed in J, measured at -30℃ on a 2 mm thick specimen according to ISO 6603-2. TM is the tensile modulus measured at 23°C according to ISO 527-2, in MPa; as well as The weight % (B) is the weight of the compatibilizer (B) in the polypropylene-polyethylene composition, expressed as a percentage by weight.

14. Articles comprising the polypropylene-polyethylene composition according to any one of claims 1 to 13.

15. The use of compatibilizer (B) in the polypropylene-polyethylene composition according to any one of claims 1 to 13 for increasing the puncture energy-stiffness (PS) balance of the polypropylene-polyethylene composition to a range of 125% to 500%, preferably in the range of 150% to 300%, of the puncture energy-stiffness (PS) balance of the blend (A). in, The puncture energy-stiffness (PS) balance is the product of the puncture energy measured at 23°C on a 2 mm thick specimen according to ISO 6603-2 and the tensile modulus measured at 23°C according to ISO 527-2.

Citation Information

Patent Citations

  • Derivatized alkylpolysilane preceramic polymers

    CA1318747C

  • Substituted phenols as stabilizers for chlorinated polymers

    CA2043931A1

  • Reduction in VOC and fog values of filled heterophasic polypropylene by separate aeration of individual polyolefin components

    EP3786190A1

  • Polypropylene - polyethylene blends with improved properties

    WO2015169690A1